The Implementation of the Merdeka Mengajar Platform and Google Workspace for Education on Teacher’s Competence - Ibnu Anwar; Syaiful Eddy; Nur Ahyani (Journal of Social Work and Science Education, 2026)
This study aimed to analyze the influence of the Merdeka Mengajar Platform and Google Workspace for Education on the professional competence of elementary school teachers in Teluk Gelam District. A quantitative research approach was employed, utilizing simple and multiple linear regression analysis to measure the individual and combined effects of the two digital platforms on teacher competence. The results demonstrate significant positive influences: (1) The Merdeka Mengajar Platform significantly affects teacher competence, accounting for 61.1% of its variance; (2) Google Workspace for Education also shows a significant effect, explaining 64.8% of the variance; (3) Together, both platforms contribute 72.3% to teacher competence, leaving 27.7% attributable to other factors not examined in this study. To optimize the benefits, it is recommended that the Ministry of Education enhance training and module development, schools establish continuous mentoring programs and provide necessary infrastructure, and teachers actively engage with these platforms for their professional growth. This study provides empirical evidence on the substantial combined impact of two major digital platforms on teacher competence within a specific Indonesian district. It quantifies their individual and synergistic contributions, offering a data-driven basis for targeted interventions and highlighting the need for integrated digital tool adoption in teacher development programs.